Bone marrow suppression in pediatric patients with differentiated thyroid cancer following empirical radioiodine therapy. Issue 31 (31st July 2020) - Dong, Ping; Wang, Li; Huang, Rui; Li, Lin
Abstract : Abstract: Pediatric patients with differentiated thyroid cancer (DTC) tend to have more advanced disease at presentation, for which more aggressive radioiodine (RAI) treatment would be commonly recommended. Several previous studies recommended dosimetry to calculate the optimal activity of RAI in pre-pubertal children and in children with a significant distant metastasis. This study aimed to evaluate the effect of empirical RAI treatment for DTC on bone marrow function in pre-pubertal children and adolescents. DTC patients aged ⩽ 18 years receiving empirical RAI treatment with complete blood count data before and after treatment were included and divided into pre-pubertal and pubertal groups. Blood count values at baseline and 1.5–3 months, 3–6 months, and 6–12 months after RAI treatment were compared. The effect of demographic, clinical, and laboratory variables on bone marrow function were assessed. We included 83 patients (113 treatments). At diagnosis, pre-pubertal children had more aggressive tumor features, including tumor size ( P  = .045) and distant metastases ( P  = .037). Approximately 51% to 96% of hypocellular bone marrow, and 11% to 14% of anemia were observed in the pre-pubertal and pubertal groups, with a majority of mild (Grade 1–2) and minority of moderate (Grade 3) bone marrow suppression. No significant differences in bone marrow function or Common Terminology Criteria for Adverse Events (CTCAE) grades were found between the pre-pubertal and pubertal groups after RAI treatment. None of the clinical factors tested were found to be significant predictors for bone marrow suppression after RAI treatment. Empirical RAI treatment for DTC in pre-pubertal children and adolescents causes mild to moderate bone marrow suppression with limited clinical significance. With adequate preparations for RAI treatment, empirical high activities (150–200 mCi) could be safe and well tolerated by both pre-pubertal and pubertal patients with DTC.